Immunotherapy for NAFLD and NAFLD-related hepatocellular carcinoma - Jeong, Seogsong; Shin, Woo-Young; Oh, Yun Hwan (Frontiers in Endocrinology, 2023)
The progression of non-alcoholic fatty liver disease (NAFLD), the most common liver disease, leads to non-alcoholic steatohepatitis and hepatocellular carcinoma. Despite the increasing incidence and prevalence of NAFLD, its therapeutic and preventive strategies to lower the disease burden is limited. In recent years, immunotherapy, including anti-programmed cell death 1/programmed cell death 1 ligand 1 treatment, has emerged as a potential approach to reach satisfactory modulation for the progression of NAFLD and treatment of NAFLD-related hepatocellular carcinoma. However, the effectiveness of immunotherapy against NAFLD and NAFLD-related hepatocellular carcinoma is in the early phase and it is yet not advanced. In addition, conflicting results are being reported regarding the prognosis of patients with NAFLD-related hepatocellular carcinoma and high expression of programmed cell death 1/programmed cell death 1 ligand 1. Herein, this review will discuss and elucidate the attempts and underlying mechanisms of immunotherapy against NAFLD and NAFLD-related hepatocellular carcinoma.